Enhancing the nutritional profile of vegan diet: a review of fermented plant-based milk as a nutritious supplement - Mohd Zaini, Nurul Solehah; Khudair, Abedelazeez J.D.; Gengan, Gengghatarani; Abd Rahim, Muhamad Hafiz; Meor Hussin, Anis Shobirin; Idris, Hamidah; Mohsin, Aliah Zannierah (Elsevier, 2023)
Plant-based milk alternatives (PBMA) has gained popularity in recent times due to their perceived superior nutritional values and its alignment with environmental and ethical concerns. However, it is important to recognize the nutrient deficiency in PBMA mainly vitamin B12, minerals, essential amino acids, and fatty acids, which can be a concern for individuals relying solely on PBMA. Nevertheless, the use of microorganisms presents an intriguing opportunity to address these limitations and enhance the nutritional profile of PBMA. Furthermore, this approach offers additional benefits in terms of gut health, promoting a more natural and holistic dietary experience. In this review, we will explore the potential of microorganisms in augmenting the nutritional values of a vegan diet. By examining the role of microorganisms in fortifying plant-based milk with essential nutrients, this review aims to provide consumers with valuable insights to make informed decisions, particularly those who adhere strictly to veganism as a way of life.